Participación Política de Mujeres en el Ámbito Local En Ecuador: ¿Qué Explican las Disparidades? - Villarreal Ojeda, Andrea (2018)
Empirical evidence has shown that men are more likely to participate in and win at local and national elections. This research analyzes the influence of gender and socioeconomic conditions at the local level on the probability of being elected as a representative of a local government. The analysis uses a Logit Model to estimate the existence of a correlation between the probability of being elected as a representative and the candidate´s characteristics such as gender, age, ethnicity and years of schooling. In addition, a regression of ordinary minimum least squares analyzes the relationship between the proportion of candidates elected in a given territory and their socioeconomic and demographic characteristics. The results suggest that women are, on average, 15% less likely to be elected than men. In addition, socioeconomic and demographic variables such as population and administrative effort influence female local participation at the municipal level, while at the provincial level these variables do not have any effect.